Effect of Using Custom Foot Orthosis on Musculoskeletal Disorders Security Bank - Syaifuddin, Muhammad; Hartatik, Chici Martinie (Poltekkes Kemenkes Surakarta, 2024)
Backgrounds: Musculoskeletal disorders are one aspect that can hinder productivity and work activity. According to the Riskesdas from 2018, non-ergonomic working postures are to blame for 8.3% of back pain, 36% of upper limb pain, and 63.3% of lower limb pain. Prevention and treatment of musculoskeletal disorders can be Standing on a softer surface can produce smooth muscle movements, reduce muscle tension, increase blood flow, reduce discomfort and fatigue, and help prevent and treat musculoskeletal disorders. For optimal weight distribution, an insole can serve as a supporting mat between the floor and the feet. Methods: This research is quantitative with one group pretest posttest pre-experimental designs. The NBM questionnaire was completed during the pre-intervention and post-intervention tests with a custom foot orthosis for observations. This study used 30 security personnel as samples. Results: The results of the Wilcoxon test, wearing a custom foot orthosis affected musculoskeletal disorders, with a significance level of 0.000 (p < 0.05). The value of reducing pain was 17.47 on average. Conclusion: When working in a standing position for too long, using a custom foot orthosis can help distribute weight more evenly and reduce pain from musculoskeletal disorders.